Advanced organic chemistry :Reaction,Mechanism,and Structure - March, Jerry (New York McGraw-Hill, 1968)
After four editions, it's still the reference students and professionals count on. Advanced Organic Chemistry Fourth Edition Only one reference has brought consistently incisive, up-to date, and comprehensive coverage of the most useful reactions in organic chemistry directly to the fingertips of both students and professionals: Advanced Organic Chemistry. Organized by reaction type, a feature that makes clear the basic principles underlying the nearly 580 reactions described, Advanced Organic Chemistry offers instant access to each reaction's scope, limitations, and mechanisms. Balancing timely detail and informative breadth, this new updated Fourth Edition: Describes the structure of organic compounds, including chemical bonding and stereochemistry Reviews general reaction mechanisms, including ordinary reactions and photochemical reactions Includes a survey of reactions, arranged by reaction type and by which bonds are broken and formed Includes IUPAC's newest system for designating reaction mechanisms Features an index to the methods used for preparing given types of compounds Contains more than 15,000 references-5,000 new to this edition-to original papers.